Comparative analysis of the susceptibility of Aedes aegypti and Japanese Aedes albopictus to all dengue virus serotypes - Daisuke Kobayashi; Izumi Kai; Astri Nur Faizah; Meng Ling Moi; Shigeru Tajima; Tomohiko Takasaki; Toshinori Sasaki; Haruhiko Isawa (Tropical Medicine and Health, 2023)
Abstract Background Dengue fever, caused by the dengue virus (DENV), is the most common viral infection transmitted by Aedes mosquitoes (mainly Ae. aegypti and Ae. albopictus) worldwide. Aedes aegypti is not currently established in Japan, and Ae. albopictus is the primary vector mosquito for DENV in the country, but knowledge of its viral susceptibility is limited. Therefore, we aimed to clarify the status of DENV susceptibility by comparing the infection and dissemination dynamics of Japanese Ae. albopictus to all known DENV serotypes with those of Ae. aegypti. Methods After propagation of each DENV serotype in Vero cells, the culture supernatants were mixed with defibrinated rabbit blood and adenosine triphosphate, and the mixture was artificially blood-sucked by two colonies of Ae. albopictus from Japan and one colony of Ae. aegypti from a dengue-endemic country (Vietnam). After 14 days of sucking, the mosquito body was divided into two parts (thorax/abdomen and head/wings/legs) and total RNA was extracted from each sample. DENV RNA was detected in these extracted RNA samples using a quantitative RT-PCR method specific for each DENV serotype, and infection and dissemination rates were analyzed. Results The Japanese Ae. albopictus colonies were susceptible to all DENV serotypes. Its infection and dissemination rates were significantly lower than those of Ae. aegypti. However, the number of DENV RNA copies in Ae. albopictus was almost not significantly different from that in Ae. aegypti. Furthermore, Japanese Ae. albopictus differed widely in their susceptibility to each DENV serotype. Conclusions In Japanese Ae. albopictus, once DENV overcame the midgut infection barrier, the efficiency of subsequent propagation and dissemination of the virus in the mosquito body was comparable to that of Ae. aegypti. Based on the results of this study and previous dengue outbreak trends, Ae. albopictus is predicted to be highly compatible with DENV-1, suggesting that this serotype poses a high risk for future epidemics in ...